Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Berpindah Ke Bank Syariah Dengan Religiusitas Sebagai Variabel Mediating (Studi Kasus pada Nasabah Bank Konvensional yang sudah berpindah ke Bank Syariah di Wilayah Kota Mataram) - Rosihan Mu’awwanah; Muady Yasin; Sahri Sahri (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
This study aims to: 1) Determine the influence of Customer Dissatisfaction on the Decision of Customers moving to Islamic Banks with Religiosity as Mediation Variables, 2) Knowing the Effect of Prices on Customers' Decisions to Switch to Islamic Banks with Religiosity as Mediation variables, 3) Knowing the Effect of Islamic Branding on Decision customers move to Islamic Banks with Religiosity as a Mediation variable. This research is a quantitative study where sampling is done by accidental sampling. The number of samples in this study were 100 respondents who are customers of conventional banks that have moved to Islamic banks. The data analysis technique used in this study is Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of WarpPLS 3.0 program. The results of this study indicate that: 1) There is a positive and significant influence of Customer Dissatisfaction with Customer Decision to move to Islamic banks through religiosity as a mediating variable with a path coefficient of 0.41 and a p-value of 0.01. 2). There is a positive and significant effect of Price on Customer Decisions to Switch to Islamic Banks through Religiosity as a mediating variable with a path coefficient of 0.22 and a p-value of 0.05. 3). There is a positive and significant influence of Islamic Branding on Customers' Decision to Switch to Islamic Banks through Religiosity as a mediating variable with a path coefficient of 0.30 and a p-value of 0.01.